Physicochemical, textural, rheological and microstructural properties of protein isolate gels produced from European eel ( Anguilla anguilla ) by heat-induced gelation process - Taktak, Wafa; Nasri, Rim; Hamdi, Marwa; Gomez-Mascaraque, Laura; Lopez-Rubio, Amparo; Li, S.M.; Nasri, Moncef; Karra-Chaâbouni, Maha (Food Hydrocolloids, 2018)
International audience